KINERJA PENDIDIKAN MENENGAH DI INDONESIA DALAM MENINGKATKAN MUTU PENDIDIKAN - Sri Winarsih (Jurnal Kependidikan, 2014)
Education is an "investment". Education is the process of forming the basis of the fundamental capabilities, both related to cognitive (intellectual) and emotional power (feeling), which is directed to human nature and to each other. Problems of teachers in secondary education in Indonesia are as follows. (1) Lack of teachers: deployment of teachers in Indonesia is not in accordance with the needs in each educational unit; there is a tendency surplus of teachers in certain areas, while other areas (outside Java) are lack of teachers. (2) The qualifications of teachers: many teachers have not their minimal education qualifications (S1 degree). (3) Academic competence and qualifications: the results of the competency test conducted on random teachers in 2004 are not satisfactory. (4) Unsuitable education background: Many teachers teach subjects that are not in accordance with their educational background. In order that the planning formulated at the national level is supported and implemented in the education ranks below, it is recommended to implement an optimal management, "Planning Philosophy", asdepicted in the "Sustainable development planning pentagon" in this article.Â Pendidikan merupakan suatu â€investasiâ€. Pendidikan merupakan proses pembentukan kemampuan dasar yang fundamental, baik menyangkut daya pikir (daya intelektual) maupun daya emosional (perasaan) yang diarahkan kepada tabiat manusia dan kepada sesamanya. Permasalahan Tenaga Pendidik di Pendidikan menengah di Indonesia adalah: (1) kekurangan guru. Penyebaran guru di Indonesia tidak sesuai dengan kebutuhan di setiap satuan pendidikan, terdapat kecenderungan surplus guru di daerah tertentu, sementara di daerah lainnya (di luar Jawa) kekurangan guru. (2) kualifikasi guru, masih banyak guru yang kualifikasi pendidikannya belum S1. (3) kualifikasi kompetensi akademik. Berdasarkan hasil uji kompetensi yangdilakukan terhadap guru secara random pada tahun 2004, hasilnya belum memuaskan. (4) Ketidaksesuaian latar belakang pendidikan dengan mata ajar. Agar perencanaan yang dirumuskan di tingkat pusat terdukung dan terlaksana pada jajaran pendidikan di bawahnya, direkomendasikan agar menerapkan manajemen secara optimal, â€œPlanning Philosophyâ€ sebagaimana tergambar dalam â€œSustainable development planning pentagonâ€ dalam artikel ini.